Efektivitas Oat Parent’s Program terhadap Kesiapan Keluarga dalam Menjalani Pengobatan TB Paru pada Anak di RS Sari Asih Ciledug - Sang Ayu Galuh; Sri Wahyuni; Apriliani Yulianti Wuriningsih (Journal of Health, Medical, and Psychological Studies, 2026)
Pulmonary tuberculosis (TB) in children remains a significant health problem in Indonesia. The success of TB treatment in children greatly depends on the involvement and readiness of the family as the primary companion during therapy. Lack of knowledge, emotional readiness, and family support can lead to non-compliance with treatment and drug resistance. The OAT Parent's Program is a family-based intervention that aims to improve parents' readiness to accompany their children undergoing TB therapy. This study aims to determine the effectiveness of the OAT Parent's Program on family readiness to undergo pulmonary TB treatment in children at the Sari Asih Ciledug Hospital children's ward. The study used a quasi-experimental design with a pre-test and post-test nonequivalent control group. The sample consisted of 60 respondents divided into an intervention group and a control group. The instruments used were questionnaires on knowledge, attitudes, actions, and family readiness. Data analysis was performed using the Wilcoxon and Mann–Whitney tests. The results showed a significant increase in family readiness after the OAT Parent's Program was administered to the intervention group (p < 0.05). This program effectively improved the knowledge, attitudes, actions, and readiness of families compared to the control group. In conclusion, the OAT Parent's Program has been proven effective in improving families' readiness to accompany their children undergoing pulmonary TB treatment.